Child With Cystic Fibrosis And Pyopneumothorax For Emergency Thoracotomy For Decortication - Rakesh Garg; Ashwani Kumar; Mridu Paban Nath; Dilip Shende; Rajib Bhattacharyya (Indian Journal of Anaesthesia, 2008)
We describe a child of cystic fibrosis for emergency thoracotomy. A 7 year female diagnosed as cystic fibrosis, pyopneumothorax with pneumonia was posted for emergency left thoracotomy. On examination, child had decreased air entry on left side of chest and bilateral crepts. Anaesthesia was induced with fentanyl, propofol, vecuronium and sevoflurane in oxygen/air. Airway was secured with tracheal tube. Central venous line and caudal epidural catheter was placed. There were multiple episodes of desaturation and airway pressures were high. Child was shifted to ICU with tube in situ and put on ventilator and gradually weaned. Epidural infusion was initiated. Child had an uneventful recovery. Patient with cystic fibrosis for emergency thoracotomy requires proper choice of anaesthetic techniques along with perioperative pain relief.